Multidisciplinary Aspects of Causality as an Ontological and Epistemological Category - Vainorenie, Iryna P.; Lemish, Nataliya Ye. (Journal of History Culture and Art Research, 2020)
The paper deals with describing a variety of interpretations of causality in different branches of modern science focusing on its multidisciplinary aspects. Moreover, historical and genetically reasoned aspects of causality in different areas are highlighted in this work. The authors take for granted that everything observable and calculable is commonly beyond dispute, and a deep understanding of causal reasoning creates an opportunity to govern different processes in various areas of human activity. Hence, interpretation of causality can be related to formal, natural, and social sciences, among which are physics, medicine, logic, philosophy, jurisprudence, psychology, and linguistics. To achieve the purpose of the paper, the authors employed such methods as observation, analysis, deduction, induction, synthesis, and description. The study proves that application of ideas obtained from physics (the hypothetical theory of a multiverse existence), logic (the implicative connection between actions), philosophy (generation of one phenomenon by another in both objective and subjective reality), psycholinguistics (the notion of mental causation), and linguistics (variety of linguistic means to express causality in different languages) shapes views of people on the interpretation of the phenomenon of causality and contributes to further comprehensive study of the causality using different approaches, linguistic inclusive. The paper also provides evidence for the causal reasoning being one of the most important mechanisms of categorization of the real world, thus making causality multidimensional. In conclusion, it is worth mentioning that modern global processes in all areas of human life demand a higher level of cross-cultural communication. The abovementioned signifies that one should be cautious in choosing language means to reflect the nuances of causal fragment of his/her worldview in order to be properly understood by speakers not only of other languages/cultures, but also by their own, for different speakers can perceive and interpret reality differently.